(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes ways to activate speech and oral speaking skills developing effective means, in particular, students’ speaking skills. The theories are presented, aimed at developing oral speech skills of students of general education school in English lesson.